Novel high-strength low-damage porous temporary plugging agent and preparation method thereof
The porous temporary plugging agent is prepared by the combination of acid anhydride, epoxy compounds, catalysts and pore-forming agents, which solves the problem of poor sealing effect of existing temporary plugging agents in high temperature and high pressure environments, and achieves a high-intensity and low-damage sealing effect, which is suitable for unconventional reservoir transformation.
Patent Information
- Application Number
- CN202510459294.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-07-18
AI Technical Summary
The existing temporary plugging agents are not blocked well in high temperature and high pressure environments and cause harm to the reservoir, making it difficult to meet the transformation needs of unconventional reservoirs.
Using a combination of acid anhydride, epoxy compounds, catalysts and pore-forming agents, a porous temporary plugging agent is prepared through heating, stirring and dissolution processes, and hydrophobic nanosilica soft particles are added to form a porous temporary plugging agent with high strength and low damage. It can dissolve at low temperature and form holes in the colloid, improving the degradation speed and sealing effect.
It realizes high-strength sealing of porous temporary plugging agent in high temperature and high pressure environment, reduces damage to the reservoir, has good fluidity and sealing performance, and is suitable for the transformation of unconventional reservoirs.
Smart Images

Figure CN120329923A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of enhanced oil and gas production and transformation, and particularly relates to a novel high-strength and low-damage porous temporary plugging agent and a preparation method thereof. Background Art
[0002] Due to the low matrix permeability of unconventional reservoirs, it is usually necessary to carry out fracturing transformation before an industrial oil and gas flow with economic benefits can be produced. However, although the production increase of some oil and gas wells is relatively large after fracturing transformation, the production decline is fast. Based on this, refracturing is usually implemented. At present, there are three ways of refracturing: creating new fractures within the formation, extending the original fractures, and turning refracturing. In recent years, major oilfields have widely adopted the turning refracturing technology in fracturing construction to increase the transformation intensity of unconventional reservoirs. And an important material in turning refracturing is the temporary plugging agent, which can temporarily block the original fractures, thereby enabling the creation of new fractures, and can be removed after the fracturing construction to ensure that the original fractures still have good permeability.
[0003] At present, temporary plugging agents can be classified into two categories according to their functions. One category is mechanical temporary plugging agents that block by physical isolation. This type of temporary plugging agent has the following deficiencies: 1) Poor selectivity, easy to leak, and unable to effectively block the formation; 2) Temperature, pressure, and acid-base properties have a great impact on its physical properties, and it is difficult to achieve the plugging of oilfields in some special environments. The other category is to block by chemical reaction, using substances generated or polymerized by chemical reactions. However, the current chemical temporary plugging agents still have the following deficiencies: 1) Most chemical temporary plugging agents are solid particles, and the effect of entering the fractures is poor, resulting in certain contingency in the plugging effect and unable to ensure the smooth injection of the temporary plugging agent into the target formation; 2) Although the current liquid temporary plugging agents can smoothly enter the fractures, the special environments such as high temperature and high pressure in the formation have a great impact on their final plugging strength, and at the same time, the final degradation effect of some liquid temporary plugging agents is poor, which will cause further damage to the reservoir. Therefore, it is necessary to develop a high-strength and low-damage temporary plugging agent to improve the development effect of unconventional reservoirs. Summary of the Invention
[0004] In view of the above problems, the present invention aims to provide a novel high-strength and low-damage porous temporary plugging agent and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] On the one hand, a preparation method of a novel high-strength and low-damage porous temporary plugging agent is provided, including the following steps:
[0007] Obtain an acid anhydride, heat and stir it until it is completely melted, then cool it to room temperature, add an epoxide and stir evenly. Subsequently, add a catalyst and stir until the catalyst is completely dissolved, and then add a pore-forming agent and stir until the pore-forming agent is completely dissolved to obtain the novel high-strength and low-damage porous temporary plugging agent.
[0008] Preferably, the acid anhydride is any one or more of methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride, tetrahydrophthalic anhydride, maleic anhydride, and benzoic anhydride.
[0009] Preferably, the epoxide is any one or more of bisphenol A diglycidyl ether, epichlorohydrin ether, epoxidized palm oil, propylene oxide, and P-(2,3-epoxypropoxy)-N,N-bis(2,3-epoxypropyl)aniline.
[0010] Preferably, the catalyst is any one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, and zinc acetylacetonate.
[0011] Preferably, the pore-forming agent is composed of a foaming agent and soft particles with a mass ratio of 1-4:1, and the soft particles are made of hydrophobic nano-silica and water.
[0012] Preferably, in parts by weight, the foaming agent includes 30-50 parts of water, 20-40 parts of sodium dodecylbenzenesulfonate, 10-12 parts of azodicarbonamide, 5-12 parts of dodecylmethylbenzylammonium chloride, 1-4 parts of biurea, 3-7 parts of sodium bicarbonate, 1-3 parts of talcum powder, 0-10 parts of ethanol, 0.5-1 part of oxalic acid, and 2-4 parts of calcium carbonate.
[0013] Preferably, the soft particles are prepared by the following steps: mixing hydrophobic nano-silica and water in a mass ratio of 98-99:1-2, and then stirring at a rotation speed of 3000-10000 rad / min for 30-60 s to obtain the soft particles; the hydrophobic nano-silica is obtained by modifying nano-silica with a silane coupling agent.
[0014] Preferably, the molar ratio of the functional groups of the acid anhydride to the epoxide is 1:0.25-2.5, the dosage of the catalyst is 0.1%-5% of the total mass of the acid anhydride and the epoxide, and the dosage of the pore-forming agent accounts for 1.5%-3% of the total mass of the porous temporary plugging agent.
[0015] On the other hand, a novel high-strength and low-damage porous temporary plugging agent is also provided, which is prepared by using the preparation method of the novel high-strength and low-damage porous temporary plugging agent described in any one of the above.
[0016] Preferably, the novel high-strength and low-damage porous temporary plugging agent is degraded into a liquid by being placed in a mixed solution of polyol and polar solvent with a mass ratio of 1:0.5-2 and under the condition of 70-200 °C.
[0017] The beneficial effects of the present invention are as follows:
[0018] The porous temporary plugging agent prepared by the present invention has a flow property and can be pumped deep into the cracks; the porous temporary plugging agent can be dissolved at a relatively low temperature, and at the same time, its residue is extremely small and the damage to the reservoir is extremely low; after the porous temporary plugging agent gels, it has a relatively high strength and can achieve a good plugging effect. Description of the Drawings
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0020] Figure 1 It is a physical diagram of the novel high-strength and low-damage porous temporary plugging agent in Example 1. Detailed Embodiments
[0021] The present invention will be further described below in conjunction with the drawings and embodiments. It should be noted that, without conflict, the embodiments in the present application and the technical features in the embodiments can be combined with each other. It should be pointed out that unless otherwise specified, all technical and scientific terms used in the present application have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present application belongs. The "including" or "comprising" and other similar words used in the present invention for disclosure mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0022] On the one hand, the present invention provides a preparation method of a novel high-strength and low-damage porous temporary plugging agent, including the following steps:
[0023] Obtain an acid anhydride, heat and stir it until it is completely melted, then cool it to room temperature, add an epoxide and stir evenly, then add a catalyst and stir until the catalyst is completely dissolved, and then add a pore-forming agent and stir until the pore-forming agent is completely dissolved to obtain the novel high-strength and low-damage porous temporary plugging agent.
[0024] In the present invention, by heating and melting the acid anhydride and then performing subsequent steps to prepare the obtained porous temporary plugging agent can have a flow property, so that it is convenient to pump the porous temporary plugging agent deep into the cracks. After the porous temporary plugging agent of the present invention gels, it has a relatively high strength and can achieve a good plugging effect. By adding the pore-forming agent, holes can be formed in the colloid formed by the porous temporary plugging agent of the present invention in the high-temperature and high-pressure environment of the formation, which helps the degradation solution to enter the colloid, thereby enhancing the degradation rate and degradation effect of the colloid. The porous temporary plugging agent of the present invention can be dissolved at a relatively low temperature, and at the same time, its residue is extremely small, and the damage to the reservoir is extremely low.
[0025] In a specific embodiment, the acid anhydride is any one or more of methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride, tetrahydrophthalic anhydride, maleic anhydride, and benzoic anhydride.
[0026] In a specific embodiment, the epoxy compound is any one or more of bisphenol A diglycidyl ether, epichlorohydrin ether, epoxidized palm oil, propylene oxide, and P-(2,3-epoxypropoxy)-N,N-bis(2,3-epoxypropyl)aniline.
[0027] In a specific embodiment, the catalyst is any one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, and zinc acetylacetonate.
[0028] In a specific embodiment, the pore-forming agent is composed of a foaming agent and soft particles with a mass ratio of 1-4:1, and the soft particles are made of hydrophobic nano-silica and water.
[0029] In the above embodiment, by adding the soft particles, the pore-forming effect of the pore-forming agent in the high-temperature and high-pressure environment of the formation can be made more excellent, and further, a large number of holes can be formed in the colloid by the porous temporary plugging agent of the present invention in the high-temperature and high-pressure environment of the formation, significantly enhancing the degradation rate and degradation effect of the colloid. And through the soft particles, the plugging performance of the porous temporary plugging agent of the present invention can be improved.
[0030] In a specific embodiment, by weight, the foaming agent includes 30-50 parts of water, 20-40 parts of sodium dodecylbenzenesulfonate, 10-12 parts of azodicarbonamide, 5-12 parts of dodecylmethylbenzylammonium chloride, 1-4 parts of biurea, 3-7 parts of sodium bicarbonate, 1-3 parts of talcum powder, 0-10 parts of ethanol, 0.5-1 part of oxalic acid, and 2-4 parts of calcium carbonate. It should be noted that the foaming agent in this embodiment is only a preferred case of the present invention, and other foaming agents in the prior art can also be applied to the present invention.
[0031] In a specific embodiment, the soft particles are prepared by the following steps: mixing hydrophobic nano-silica and water in a mass ratio of 98 - 99:1 - 2, and then stirring for 30 - 60 s under the condition of a rotation speed of 3000 - 10000 rad / min to obtain the soft particles; the hydrophobic nano-silica is obtained by modifying nano-silica with a silane coupling agent.
[0032] It should be noted that hydrophobic nano-silica is a prior art. The method of modifying nano-silica with a silane coupling agent in the above embodiment is only a preferred preparation method of hydrophobic nano-silica. Other methods for preparing the hydrophobic nano-silica, such as heat treatment, plasma treatment, graft modification, etc., can also be applied to the present invention. The higher the hydrophobic property of the hydrophobic nano-silica, the more stable the obtained soft particles, the higher the pore formation rate of the novel high-strength and low-damage porous temporary plugging agent of the present invention, and the influence on the pressure-bearing capacity changes little.
[0033] In a specific embodiment, the hydrophobic nano-silica is prepared by the following steps:
[0034] Mix 10 - 100 parts of silicon tetrachloride, 50 - 150 parts of ethanol, 1 - 10 parts of deionized water and 1 - 10 parts of ammonia water, and carry out a hydrolysis reaction at a temperature of 50 - 80 °C for 30 - 240 min to obtain a nano-silica suspension;
[0035] Add 5 - 20 parts of a silane coupling agent to the nano-silica suspension, and then carry out a hydrolysis and condensation reaction under constant temperature stirring at 20 - 80 °C for 60 - 180 min; the silane coupling agent is any one or more of trimethylchlorosilane, 3-mercaptopropyltriethoxysilane, dimethyldiethoxysilane, and dimethyldichlorosilane;
[0036] Filter and dry the product after the hydrolysis and condensation reaction to obtain the hydrophobic modified nano-silica.
[0037] It should be noted that the method of modifying nano-silica with a silane coupling agent is a prior art. The method of modifying nano-silica with a silane coupling agent in the above embodiment is only a preferred preparation method of the present invention. Other methods of modifying nano-silica with a silane coupling agent in the prior art can also be applied to the present invention.
[0038] In a specific embodiment, the molar ratio of the functional groups of the acid anhydride to the epoxide is 1:0.25 - 2.5, the dosage of the catalyst is 0.1% - 5% of the total mass of the acid anhydride and the epoxide, and the dosage of the pore-forming agent accounts for 1.5% - 3% of the total mass of the porous temporary plugging agent.
[0039] On the other hand, the present invention also provides a novel high-strength and low-damage porous temporary plugging agent, which is prepared by using the preparation method of the novel high-strength and low-damage porous temporary plugging agent described in any one of the above.
[0040] In a specific embodiment, the novel high-strength and low-damage porous temporary plugging agent is degraded into a liquid by being placed in a mixed solution of polyol and polar solvent with a mass ratio of 1:0.5 - 2 and under the condition of 70 - 200 °C.
[0041] Optionally, the polar solvent is any one of ethanol, tetrahydrofuran, N,N'-dimethylformamide, and N,N'-dimethylacetamide.
[0042] It should be noted that only using ethanol, etc. can also degrade the novel high-strength and low-damage porous temporary plugging agent, but ethanol is not very suitable for large-scale use at the construction site due to its flammable characteristics. Therefore, in the above embodiment, the present invention degrades the novel high-strength and low-damage porous temporary plugging agent of the present invention by using a mixed solution of polyol and polar solvent, which can be more suitable for actual working conditions.
[0043] Example 1
[0044] A novel high-strength and low-damage porous temporary plugging agent is prepared by the following steps:
[0045] (1) Weigh 10 g of hexahydrophthalic anhydride, heat and stir until completely melted, and then cool to room temperature to obtain solution A;
[0046] (2) Weigh 5 g of bisphenol A diglycidyl ether, add it to the solution A, and stir evenly to obtain solution B;
[0047] (3) Weigh 0.2 g of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, add it to the solution B, and then stir until the 1,5,7-triazabicyclo[4.4.0]dec-5-ene is completely dissolved to obtain a mixed solution C;
[0048] (4) Weigh 40 g of water, 20 g of sodium dodecylbenzenesulfonate, 10 g of azodicarbonamide, 8 g of dodecylmethylbenzylammonium chloride, 2 g of biurea, 6 g of sodium bicarbonate, 1 g of talcum powder, 0.5 g of oxalic acid, and 2 g of calcium carbonate, mix them evenly to obtain a foaming agent D;
[0049] (5) Weigh 40 g of silicon tetrachloride, 100 g of ethanol, 10 g of deionized water, and 10 g of ammonia water, mix them, and react in an environment at a temperature of 60 °C for 120 min to obtain a nano-silica suspension. Then add 10 g of trimethylchlorosilane to the nano-silica suspension, and then stir at a constant temperature of 50 °C for 60 min, filter and dry to obtain hydrophobic nano-silica;
[0050] (6) Weigh 98 g of water and 2 g of hydrophobic nano-silica, and stir for 60 s under the condition of a rotation speed of 6000 rad / min to obtain soft particles E;
[0051] (7) Weigh 0.25 g of the foaming agent D and 0.25 g of the soft particles E, add them to the mixed solution C, and mix evenly to obtain the novel high-strength and low-damage porous temporary plugging agent.
[0052] Example 2
[0053] (1) Weigh 6 g of methyltetrahydrophthalic anhydride and 6 g of hexahydrophthalic anhydride, heat and stir until completely melted, and then cool to room temperature to obtain solution A;
[0054] (2) Weigh 4 g of bisphenol A diglycidyl ether, add it to the solution A, and stir evenly to obtain solution B;
[0055] (3) Weigh 0.25 g of 4-dimethylaminopyridine, add it to the solution B, and then stir until the 4-dimethylaminopyridine or zinc acetylacetonate is completely dissolved to obtain a mixed solution C;
[0056] (4) Weigh 40 g of water, 20 g of sodium dodecylbenzenesulfonate, 10 g of azodicarbonamide, 8 g of dodecylmethylbenzylammonium chloride, 2 g of biurea, 6 g of sodium bicarbonate, 1 g of talc powder, 0.5 g of oxalic acid, and 2 g of calcium carbonate, and mix evenly to obtain the foaming agent D;
[0057] (5) Mix 40 g of silicon tetrachloride, 100 g of ethanol, 10 g of deionized water and 10 g of ammonia water, react in an environment at a temperature of 60 °C for 120 min to obtain a nano-silica suspension, then add 10 g of trimethylchlorosilane to the nano-silica suspension, and then stir at a constant temperature of 50 °C for 60 min, filter and dry to obtain hydrophobic nano-silica;
[0058] (6) Weigh 98 g of water and 2 g of hydrophobic nano-silica, and stir for 60 s under the condition of a rotation speed of 6000 rad / min to obtain soft particles E;
[0059] (7) Weigh 0.3 g of the foaming agent D and 0.2 g of the soft particles E, add them to the mixed solution C, and mix evenly to obtain the novel high-strength and low-damage porous temporary plugging agent.
[0060] Example 3
[0061] Different from Example 1, the foaming agent in step (4) of this example is a conventional foaming agent. Step (4) of this example is as follows: Weigh sodium dodecyl sulfate and sodium bicarbonate according to a mass ratio of 1:0.5, mix them evenly to obtain foaming agent D.
[0062] Comparative Example 1
[0063] Different from Example 1, no pore-forming agent is added in this comparative example, that is, steps (4)-(7) are not carried out, and the mixed liquid C obtained in step (3) is the temporary plugging agent of this comparative example.
[0064] Comparative Example 2
[0065] Different from Example 1, the foaming agent in the pore-forming agent is not added in this comparative example, that is, step (4) is not carried out. In step (7), only 0.25 g of the soft particles E is weighed and added to the mixed liquid C, and mixed evenly to obtain a temporary plugging agent.
[0066] Comparative Example 3
[0067] Different from Example 1, the soft particles in the pore-forming agent are not added in this comparative example, that is, steps (5)-(6) are not carried out. In step (7), only 0.25 g of the foaming agent D is weighed and added to the mixed liquid C, and mixed evenly to obtain a temporary plugging agent.
[0068] Test Example
[0069] Observe the state of the novel high-strength and low-damage porous temporary plugging agent prepared in each example of the present invention. The finished product prepared in Example 1 is as Figure 1 shown, and the states of the finished products prepared in other examples are similar. It can be seen from Figure 1 this that the novel high-strength and low-damage porous temporary plugging agent of the present invention has fluidity, which can facilitate its pumping to the deep part of the crack to achieve deep temporary plugging.
[0070] Place the temporary plugging agents of each example and each comparative example in an environment of 5 MPa and 120 °C, let them stand for 20 min, and finally measure the overall colloid porosity. The results are shown in Table 1:
[0071] Table 1 Porosity test results of the temporary plugging agents of each example and each comparative example
[0072] temporary plugging agent Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 pore ratio 32% 37% 28% 0% 5% 8%
[0073] It can be seen from Table 1 that the temporary plugging agent without adding a pore-forming agent cannot form pores. And the overall porosities of only adding the foaming agent in the pore-forming agent and only adding the soft particles in the pore-forming agent are both small.
[0074] Place the cored rock with slits opened and proppant placed therein into a core holder, heat it up to 120 °C, and use the constant flow and constant pressure pump of the core temporary plugging tester to displace the temporary plugging agents of each example and each comparative example respectively at an injection rate of 5 mL / min. Keep the annulus pressure always greater than the plugging pressure by 3 MPa, and record the maximum bearing pressure (due to the limitation of the constant flow and constant pressure pump, the maximum pressure applied is 40 MPa). The test results are shown in Table 2:
[0075] Table 2 Test results of the pressure-bearing capacity of the temporary plugging agents of each example and each comparative example
[0076] temporary plugging agent Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 pressure bearing capacity 40MPa 40MPa 35.4MPa 20.5MPa 26.3MPa 30.4MPa
[0077] As can be seen from Table 2, the novel high-strength and low-damage porous temporary plugging agent described in the present invention has excellent pressure-bearing performance, all greater than 35.4 MPa, and the novel high-strength and low-damage porous temporary plugging agent prepared with the foaming agent preferably selected in the present invention can also withstand a high pressure of 40 MPa. However, for the temporary plugging agent in Comparative Example 1 without a pore-forming agent, the breakthrough pressure is only 20.5 MPa, and for the temporary plugging agent in Comparative Example 2 with only soft particles in the pore-forming agent added, the breakthrough pressure is 26.3 MPa, and for the temporary plugging agent in Comparative Example 3 with only the foaming agent in the pore-forming agent added, the breakthrough pressure is 30.4 MPa, all of which cannot reach the pressure-bearing performance achievable by the present invention.
[0078] Place the temporary plugging agents of each example and each comparative example into 25 g of ethanol respectively, then place them in an oven at 100 °C and let them stand for 6 h, and observe their overall dissolution situation. The results are shown in Table 3:
[0079] Table 3 Degradation test results of the temporary plugging agents of each example and each comparative example
[0080] temporary plugging agent Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 residual mass 0.23% 0.41% 1.32% 18.1% 13.71% 9.8%
[0081] As can be seen from Table 3, the residual mass of the novel high-strength and low-damage porous temporary plugging agent described in the present invention after 6 h of degradation is less than 2%, and the degradation effect is good.
[0082] In summary, the present invention can provide a high-strength and low-damage porous temporary plugging agent with flow properties capable of achieving deep temporary plugging. Compared with the prior art, the present invention has made remarkable progress.
[0083] The above are only representative embodiments of the present invention, and do not impose any form of limitation on the present invention. Any person skilled in the art, without departing from the scope of the technical solution of the present invention, makes some modifications or variations using the technical content disclosed above, and such embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent change, and variation made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A preparation method of a novel high-strength and low-damage porous temporary plugging agent, characterized in that, It includes the following steps: Obtain an acid anhydride, heat and stir it until it is completely melted, then cool it to room temperature, add an epoxide and stir evenly, then add a catalyst and stir until the catalyst is completely dissolved, and then add a pore-forming agent and stir until the pore-forming agent is completely dissolved to obtain the novel high-strength and low-damage porous temporary plugging agent.
2. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to claim 1, wherein The acid anhydride is any one or more of methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride, tetrahydrophthalic anhydride, maleic anhydride, and benzoic anhydride.
3. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to claim 1, characterized in that, The epoxide is any one or more of bisphenol A diglycidyl ether, epichlorohydrin ether, epoxidized palm oil, propylene oxide, and P-(2,3-epoxypropoxy)-N,N-bis(2,3-epoxypropyl)aniline.
4. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to claim 1, wherein, The catalyst is any one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 4-dimethylaminopyridine, and zinc acetylacetonate.
5. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to claim 1, characterized in that The pore-forming agent is composed of a foaming agent and soft particles with a mass ratio of 1-4:1, and the soft particles are made of hydrophobic nano-silica and water.
6. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to claim 5, characterized in that, By weight, the foaming agent includes 30-50 parts of water, 20-40 parts of sodium dodecylbenzenesulfonate, 10-12 parts of azodicarbonamide, 5-12 parts of dodecylmethylbenzylammonium chloride, 1-4 parts of biurea, 3-7 parts of sodium bicarbonate, 1-3 parts of talcum powder, 0-10 parts of ethanol, 0.5-1 part of oxalic acid, and 2-4 parts of calcium carbonate.
7. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to claim 5, wherein, The soft particles are prepared through the following steps: Mix hydrophobic nano-silica and water at a mass ratio of 98-99:1-2, and then stir at a rotation speed of 3000-10000 rad / min for 30-60 s to obtain the soft particles; the hydrophobic nano-silica is obtained by modifying nano-silica with a silane coupling agent.
8. The preparation method of the novel high-strength and low-damage porous temporary plugging agent according to any one of claims 1-7, characterized in that, The molar ratio of the functional groups of the acid anhydride to the epoxide is 1:0.25-2.5, the dosage of the catalyst is 0.1%-5% of the total mass of the acid anhydride and the epoxide, and the dosage of the pore-forming agent accounts for 1.5%-3% of the total mass of the porous temporary plugging agent.
9. A novel high-strength and low-damage porous temporary plugging agent, characterized in that, It is prepared by using the preparation method of the novel high-strength and low-damage porous temporary plugging agent described in any one of claims 1-8.
10. The novel high-strength and low-damage porous temporary plugging agent according to claim 9, wherein, The novel high-strength and low-damage porous temporary plugging agent degrades into a liquid by being placed in a mixed solution of a polyol and a polar solvent with a mass ratio of 1:0.5-2 at 70-200 °C.